METAFORA "CLOTHING" AS A NATURE OF NATURE IN READING BUTON PEOPLE IN THE TRANSLATION OF AJONGA YINDA MALUSA'S WORKS BY SYEKH HAJI ABDUL GANIU - Ali Mukti; Siti Gomo Attas; Eva Leiliyanti (Indonesian EFL Journal, 2022)
The purpose of this study is to describe the metaphor in the translation of Ajonga Yinda Malusa's manuscript by Sheikh Haji Abdul Ganiu. This research uses content analysis method (content analysis). By using Metaphor theory according to Lakoft Johnson. As the results in this research are: the shame metaphor is a noble trait of clothing that never fades, the fear metaphor is a trait that requires trepidation Referring to something that is considered to bring disaster a metaphor full of nature with the meaning of loyalty and sincerity, the metaphor of shyness not just talking and from origin, everything that will be talked about and done is looking more for it.Keywords: manuscripts; matafora; noble attributes.